THE REAL PROBLEM OF FEMICIDE - Torres Mantilla, Marcelo Manuel (2024)
In the present work I will try to explain two lines of interpretation of the discussed article that regulates the crime of feminicide in our Penal Code, making known the consequences that would follow from accepting them, in addition to some objections to them. Much of the essay will examine the best interpretation of the criminal offense and then the strongest objection that must be faced; I consider the latter the real problem of feminicide. Finally, I will suggest an interpretation of feminicide and the conclusions will be compiled.